Endoscopic Ultrasound-Guided Biliary Drainage in Two Patients with Difficult Biliary Access - Libânio, D (2018)
INTRODUCTION: Endoscopic retrograde cholangiopancreatography is the method of choice for biliary drainage, although in some cases standard biliary access is difficult or even impossible. Endoscopic ultrasound (EUS)-guided endoluminal procedures are an alternative in these cases, although experience with these techniques is still limited. CLINICAL CASE: We present two cases of successful EUS-guided biliary drainage. In the first case, a hepaticogastrostomy was performed in a patient with stage IV gastric adenocarcinoma with obstructive jaundice due to compression of the hilum, where malignant gastric stenosis and previous palliative gastrojejunostomy precluded access to the second part of the duodenum. In the second case, a patient with a pancreatic head adenocarcinoma with duodenal invasion that precluded major papillae identification was submitted to a choledochoduodenostomy. Both procedures occurred without immediate or delayed adverse events, with technical and clinical success. DISCUSSION: Although experience with EUS-guided biliary drainage is still limited, its efficacy and safety is favorable when compared with percutaneous and surgical drainage, and should be considered an alternative to these techniques where sufficient expertise exists.